Development of a Prognostic Signature Based on Single-Cell RNA Sequencing Data of Immune Cells in Intrahepatic Cholangiocarcinoma - Su, Miao; Qiao, Kuang-Yuan; Xie, Xiao-Li; Zhu, Xin-Ying; Gao, Fu-Lai; Li, Chang-Juan; Zhao, Dong-Qiang (Frontiers in Genetics, 2021)
Analysis of Single-cell RNA sequencing (scRNA-seq) data of immune cells from tumor microenvironment (TME) may screen out biomarkers that determine the tumor progression. The study aimed to investigate the prognostic value of differentially expressed genes (DEGs) based on scRNA-seq for intrahepatic cholangiocarcinoma (ICC). We downloaded scRNA-seq data of 33991 cell samples comprising of 17090 ICC cell samples and 16901 ICC adjacent tissue cell samples regarded as normal cells. The scRNA-seq data were processed and finally were classified into twenty clusters. The clusters consisting of immune cells were extracted and processed again in the same way, respectively, and each type of immune cells can be further divided into several subclusters. Totally 337 marker genes of macrophages were screened out by comparing ICC subclusters with normal subclusters, and 427 marker genes of B cells were acquired by comparing subclusters between ICC tissue and normal tissue. Finally 659 DEGs were obtained by merging the marker genes of B cells and those of macrophages together. Clinical information and Gene expression data of ICC samples were downloaded. Nine prognosis-related genes (PRGs) signature was established by analyzing the correlation between DEGs and overall survival (OS) of ICC. The robustness and validity of the signature were also verified. Functional enrichment analysis revealed that nine PRGs were mainly involved in immune mechanisms of tumor. In conclusion, this study established a PRGs signature based on scRNA-seq data of immune cells for ICC patients, which not only reflected the TME immune status but also provided new biomarkers for ICC prognosis.